دور التخطيط الاستراتيجي في تحقيق التميز في أداء الإدارة الرياضية - بن ربيع ، جمال; Supervisor : قروش ، النواري (Mohamed Boudiaf University of M'Sila, 2025)
الملخص : بالعربية(عبارة عن فقرة) تهدف هذه الدراسة إلى تسليط الضوء على الدور الحيوي الذي يلعبه التخطيط الاستراتيجي في تعزيز كفاءة وفعالية الإدارة الرياضية، باعتبارها أحد العوامل الأساسية في تحقيق التميز المؤسسي والنجاح المستدام للهيئات والمنظمات الرياضية. وقد تم التركيز على تحليل مكونات التخطيط الاستراتيجي (مثل: تحديد الرؤية، صياغة الأهداف، التحليل البيئي، تحديد البدائل، ووضع خطط التنفيذ والمتابعة) ودورها في توجيه الأنشطة الرياضية نحو تحقيق أهداف واضحة وقابلة للقياس. اعتمدت الدراسة على المنهج الوصفي من خلال مراجعة الأدبيات والدراسات السابقة، مع الاستفادة من النماذج التطبيقية في إدارات رياضية ناجحة. وقد أظهرت النتائج أن وجود خطة استراتيجية واضحة يسهم في تحسين الأداء الإداري، رفع جودة اتخاذ القرار، تعزيز الكفاءة التنظيمية، وتحقيق رضا الأطراف المعنية. عنوان الدراسة : دور التخطيط الاستراتيجي في تحقيق التميز في أداء الإدارة الرياضية أهداف الدراسة :. - الكشف عن مدى وضوح المفهوم العلمي للتخطيط الاستراتيجي في إدارة الموارد البشرية في المؤسسات الرياضية الجزائرية وتأثير ذلك على درجة ممارستهم للأنشطة المتعلقة بالتخطيط للموارد البشرية. - التعرف على واقع عملية التخطيط السليم لتنمية التميز في ظل التخطيط الاستراتيجي في المؤسسات الرياضية. - إمكانية إظهار كيفية التفاعل الاستراتيجي بين تخطيط الموارد البشرية وباقي أنشطة الموارد البشرية. - إبراز المعوقات التي تحد وتعيق تحقيق التخطيط لتنمية الموارد البشرية في ظل التخطيط الاستراتيجي في المؤسسات الرياضية. التساؤل العام الدراسة : -هل دور التخطيط الاستراتيجي دور في تحقيق التميز في أداء الإدارة الرياضية؟ التساؤلات الجزئية : 1. هل دراسة الوسائل والأهداف تساهم في تحقيق التميز داخل المنشآت الرياضية؟ 2. هل دراسة سياسة المشروع تساهم في تحقيق التميز داخل المنشآت الرياضية؟ 3. هل توجيهات الادارة تساهم في تحقيق التميز داخل المنشآت الرياضية؟ الفرضية العامة للدراسة : - للتخطيط الاستراتيجي دور في تحقيق التميز في أداء الإدارة الرياضية. الفرضيات الجزئية 1. لدراسة الوسائل والأهداف دور في تحقيق التميز داخل المنشآت الرياضية. 2. لدراسة سياسة المشروع دور في تحقيق التميز داخل المنشآت الرياضية. 3. لتوجيهات الادارة دور في تحقيق التميز داخل المنشآت الرياضية. المنهج المتبع في الدراسة : المنهج الوصفي الأدوات المستخدمة في الدراسة الاستبيان الكلمات المفتاحية بالعربية: التخطيط، التخطيط الاستراتيجي، التميز، الإدارة الرياضية. بالإنجليزية Planification, planification stratégique, excellence, gestion sportive. جاء هذا البحث في فصول . الفصل الأول: الإطار العام للدراسة وتناول الفصل الثاني: التخطيط الاستراتيجي أما الفصل الثالث: الأداء المتميز الفصل الرابع: منهجية الدراســــــــة الفصل الخامس: عرض وتحليل ومناقشة النتائج الفصل السادس: الاستنتاجات والاقتراحات من أهم النتائج التي توصل إليها الباحث: بعد تحليل نتائج الفرضية الأولى التي تنص على أن دراسة الوسائل والأهداف تساعد في تحقيق التميز بالمنشأة الرياضية وهذا ما يبرز أهمية دراسة الوسائل الممكنة لتحقيق الأهداف المسطرة إذ لا يمكن تحقيق الأهداف إلا من خلال دراسة علمية دقيقة. وبعد تحليل نتائج الفرضية الثانية والتي تنص على دور دراسة سياسة المشروع في تحقيق التميز بالمنشأة الرياضية، إذ تساعد دراسة السياسة المتبعة في إيجاد صياغة مناسبة للخطة الإستراتيجية من طرف صناع القرار. وانطلاقا من تحليل الفرضية الثالثة والتي تنص على مساهمة توجيهات الإدارة في تحقيق التميز بالمنشأة الرياضية، إذ تلعب توجيهات المسؤولين دورا بارزا في تسهيل عملية التخطيط الإستراتيجي لدى الموظفين. أهم التوصيات: - وضع طرق أكثر فعالية وإيجابية لصنع القرار بالمنشأة الرياضية. - تطوير الجانب الإداري بالمنشأة الرياضية من خلال اعتماد تقنيات تكنولوجية جديدة من شأنها أن تقلل من الإجراءات الإدارية التي تثقل كاهل الإدارة القائمة على المنشأة الرياضية بصفة عامة، ومحاولة تحديد مهام الموظفين بدقة، وتجسيد سلوك إبداعي يسهم في تقديم خدمات ذات جودة عالية على مستوى هذه المنشآت. - قيام المسؤولين في المنشآت الرياضية بعقد لقاءات دورية مع الموظفين لتعريفهم بأهمية ودواعي تطبيق التخطيط الإستراتيجي داخل المنشأة الرياضية. Searchlight in English Faculty Institute of Sciences and Sports and Technical and Physical Department: Sports Management and Administration Serial Number: UN2801202406064089172 Registration Number: [To be filled] Student: Ben Rabia Djamel Date of Defense: June 11, 2025 Thesis Title: The Role of Strategic Planning in Achieving Excellence in Sports Management Performance Thesis Language: Arabic Thesis Type: Master’s Country: People's Democratic Republic of Algeria – Wilaya of M’sila University: Mohamed Boudiaf University of M’sila Supervisor: Professor Karrouche Enouari Number of Pages: 99 Digital Format: Word & PDF Division: Sports Management and Administration Specialization: Human Resources and Sports Facilities Management Abstract (in English) This study aims to highlight the vital role played by strategic planning in enhancing the efficiency and effectiveness of sports management, considering it as one of the fundamental pillars for achieving institutional excellence and sustainable success for sports organizations. The focus was placed on analyzing the components of strategic planning (such as defining vision, formulating objectives, environmental analysis, identifying alternatives, and implementing and monitoring plans) and their role in directing sports activities toward achieving clear and measurable goals. The study adopted the descriptive method by reviewing literature and previous research, as well as drawing from practical models in successful sports administrations. The results showed that having a clear strategic plan contributes to improved administrative performance, higher quality decision-making, enhanced organizational efficiency, and increased satisfaction among stakeholders. Study Title The Role of Strategic Planning in Achieving Excellence in Sports Management Performance Study Objectives • To explore the extent to which the scientific concept of strategic planning is understood in human resource management within Algerian sports institutions, and how this affects their level of engagement in human resource planning activities. • To identify the current state of proper planning to promote excellence within the framework of strategic planning in sports institutions. • To examine how human resource planning interacts strategically with other HR functions. • To highlight the obstacles hindering the development of human resources within the context of strategic planning in sports institutions. General Research Question Does strategic planning play a role in achieving excellence in sports management performance? Sub-Questions 1. Does studying means and objectives contribute to achieving excellence within sports facilities? 2. Does studying project policies contribute to achieving excellence within sports facilities? 3. Do administrative directives contribute to achieving excellence within sports facilities? General Hypothesis Strategic planning plays a role in achieving excellence in sports management performance. Sub-Hypotheses 1. Studying means and objectives plays a role in achieving excellence within sports facilities. 2. Studying project policies plays a role in achieving excellence within sports facilities. 3. Administrative directives play a role in achieving excellence within sports facilities. Research Methodology Descriptive method Data Collection Tool Questionnaire Keywords Planning, Strategic Planning, Excellence, Sports Management Structure of the Thesis • Chapter 1: General Framework of the Study • Chapter 2: Strategic Planning • Chapter 3: Distinguished Performance • Chapter 4: Study Methodology • Chapter 5: Presentation, Analysis, and Discussion of Results • Chapter 6: Conclusions and Recommendations Key Findings • First Hypothesis: Studying the means and objectives contributes to achieving excellence in sports institutions, demonstrating the importance of scientifically analyzing available resources to meet predefined goals. • Second Hypothesis: Studying project policies contributes to excellence, as it helps decision-makers design suitable strategic plans. • Third Hypothesis: Administrative directives significantly support strategic planning by facilitating implementation among employees. Key Recommendations • Develop more effective and positive decision-making methods in sports institutions. • Improve administrative operations through the adoption of new technologies to reduce bureaucratic burdens and precisely define employee roles, fostering creativity and high-quality service delivery. • Organize periodic meetings between managers and employees to explain the importance and rationale of implementing strategic planning in sports institutions.
Keywords: التخطيط; التخطيط الاستراتيجي; التميز; الإدارة الرياضية